State Policy for the Private Healthcare Sector Development of Ukraine - Olena Kolotilina; Vitalii Lomko; Lesya Prasol (Health Economics and Management Review)
The need to ensure quality and comprehensive healthcare at the world standard level determines the establishment and importance of private medicine in the healthcare system. It forms the task to reform, develop, and implement targets for private medicine. This article aims to investigate the measures by state policy in promoting private medical services. The methodological basis of this study is the dialectical method of scientific knowledge, system approach, and methods of logistic analysis. The empirical research involved retrospective, structural and comparative analyses. To achieve the study goal, the following tasks were solved: 1) determination of the theoretical basis of the state policy in private healthcare based on scientific background; 2) the analysis of the state policy in Ukrainian healthcare; 3) identification of the role of private medicine in the health care system; 4) the comprehensive analysis of the medical institution activities on the example of a private clinic «L-MED Clinic»; 5) determination of the connection between the effectiveness of activities and the marketing activities in promoting medical services. is study determined the importance of private medicine in the healthcare system of Ukraine. Private treatment and prevention facilities relieve the burden on public hospitals and clinics. The main competitive advantages of private healthcare institutions include availability, sufficient admission time, responsibility and organized attitude to the treatment process, quality diagnosis, full-range medical services, courtesy and attentive staff, comfortable and pleasant interior, etc. Based on the findings, the authors provided practical recommendations for improving the state policy, state regulation of private medical activity, and implementing the best world practices of branching out of the health care sector. The obtained results could be useful to the Ministry of Health of Ukraine, the Ministry of Social Policy of Ukraine, the Cabinet of Ministers of Ukraine, and the Verkhovna Rada of Ukraine in state regulation of healthcare reformation in Ukraine.